Alexis Wright's The Swan Book (2013) as 'crisis fiction'. Issue 9 (2nd September 2022) - Neave, Lucy
ABSTRACT: Alexis Wright's novel The Swan Book (2013) has been read as contesting imperialist histories in its use of ironic magical realism: asengaging with debates in Australian indigenous communities about sovereignty; and, as world-making in its portrayal of conflicting and overlapping material forces and temporalities. Previous readings have examined the text's dramatisation of biopolitical interventions into the lives of Aboriginal people, and the novel's near-simultaneous evocation of different time periods. To date, scholarship on The Swan Book has not fully conceptualised its assault on western narrative forms. The following paper focuses on the novel's contestation of crisis and catastrophe as metonyms for colonial and western ways of being and knowledge, and its narratival focus on what could be termed 'survivance', a term used (after Derrida) by Native American fiction writer and scholar Gerald Vizenor, to whose novel Bearheart: The Heirship Chronicles (1990), Wright's book makes intertextual references. The following paper contends that Wright's novel offers radical structures of feeling that counter western notions of narrative, history, time and the individual. These are manifest in the text's inclusion of nested narratives, its critique of western notions of history, its de-hierarchisation of time, and in its disputation of the centrality of the individual.